The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1017/s0263574719001802
|View full text |Cite
|
Sign up to set email alerts
|

Velocity and Force Transfer Performance Analysis of a Parallel Hip Assistive Mechanism

Abstract: SUMMARYAgainst the backdrop of accelerated ageing around the globe, an increasing number of individuals suffer from hip motion disability and gait disorders. In this paper, the performance analysis of a novel parallel assistive mechanism with 2 DOF for hip adduction/abduction (AB/AD) and flexion/extension (FL/EX) assistance is completed and evaluated, particularly the velocity and force transfer features. The analysis shows that the assistive mechanism has advantages of fine motion assistive isotropy, high for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Jiang et al, 8 Lu et al, 9 Liu 10 and Liu 11 designed a V -shaped TBM that can achieve a small turning radius based on the stewart platform, and concluded that the V -type TBM has good geological adaptability and efficient mechanized construction. Wang et al, 12 Yuan 13 and Li et al 14 proposed that the smaller the turning radius of TBM small curve, the greater the amount of correction, the lower the correction accuracy, and checked the factors affecting the construction of small curve. Yu et al, 15 Tian et al 16 analyzed the kinematic coupling degree and force transfer performance of V -type and Π-type TBM and the force transfer performance of the propulsion system, and concluded that V -type TBM was better than Π-type TBM.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al, 8 Lu et al, 9 Liu 10 and Liu 11 designed a V -shaped TBM that can achieve a small turning radius based on the stewart platform, and concluded that the V -type TBM has good geological adaptability and efficient mechanized construction. Wang et al, 12 Yuan 13 and Li et al 14 proposed that the smaller the turning radius of TBM small curve, the greater the amount of correction, the lower the correction accuracy, and checked the factors affecting the construction of small curve. Yu et al, 15 Tian et al 16 analyzed the kinematic coupling degree and force transfer performance of V -type and Π-type TBM and the force transfer performance of the propulsion system, and concluded that V -type TBM was better than Π-type TBM.…”
Section: Introductionmentioning
confidence: 99%
“…Performance evaluation for the parallel mechanism is a significant issue in real industrial application [17]; thus, some indices have been proposed to evaluate the workspace [18][19][20], stiffness [21], and other aspects [22][23][24] of the mechanism. In this case, the performance analysis of reconfigurable parallel mechanisms has also gained interests.…”
Section: Introductionmentioning
confidence: 99%